Early history of clinical application of photosensitizing drugs in photodynamic therapy (PDT) of portwine stain (PWS) birthmarks - Kaihua Yuan; Zheng Huang (Photodiagnosis and Photodynamic Therapy)
It has been known for two decades that vascular acting PDT can be used as an alternative in the treatment of portwine stain (PWS) birthmarks. The modality is only used in China at the moment and an expert consensus has been published this year. A recent review article in Lasers in Surgery and Medicine summarized the available evidence based on PubMed records of PWS treatment using pulsed dye laser (PDL) and HMME-PDT. The authors observed that HMME-PDT has emerged as the first choice for PWS treatment, particularly for young children, in many major hospitals in China. The authors also raised questions on ethics of several Chinese reports. This correspondence addresses these questions and meanwhile explains the early history of clinical application of photosensitizing drugs in PWS PDT in China.